DAMPAK PENERAPAN METODE KONSELING ISLAMI TERHADAP SELF DISCIPLINE PESERTA DIDIK KELAS VIII D MTs. AL – MISRI TA. 2015/2016 DESA CURAHMALANG KECAMATAN RAMBIPUJI KABUPATEN JEMBER - Miftahul Jannah; Arifin Nur Budiono; Siti Rahayu (FKIP Universitas Islam Jember, 2016)
This pre-experimental design explored the effects of Islamic counselling approach on the students’ self-discipline at class VIIID, MTs. Al-Misri Rambipuji-Jember, in the academic year 2015/2016. The author employed one group pretest-posttest design. The methods adopted were questionnaire, interview, and documentation. The results of Z-test of the implementation of Islamic counselling approach after being calculated using Wilcoxon signed rank test at the .05 significance level showed -1.2135976which indicated that Z score was greater than Z-Table. It also indicated that H1 was accepted and H0 was rejected. Thus, it could be concluded that the implementation of Islamic counselling approach had a significant effect on the students’ self-discipline.Keyword: Islamic counseling, self discipline